A case study on the implementation of quality and comprehensive indicators set in routine diabetes care - Ana Cristina García-Ulloa; José Luis Cárdenas-Fragoso; Diana Hernández-Juárez; Nancy Haydée Serrano-Pérez; Paula Blancarte-Jaber; Carlos Aguilar-Salinas; Nancy R. Mejía-Domínguez; Alejandro Zentella-Dehesa; Sergio Hernández-Jiménez; for the Group of Study CAIPaDi (BMC, 2024)
Abstract Introduction Type 2 diabetes is a major public health issue in Mexico due to its high prevalence and its projection for the coming years for this disease. Findings on multidisciplinary care related to chronic diseases have proven effective, based on measurement of patient-centered outcomes, The Center of Comprehensive Care for Patients with Diabetes (CAIPaDi) is a multidisciplinary program focused on reducing diabetes complications. This case study aims to illustrate the results of implementing health outcomes measurements and demonstrate the beneficial effects of establishing a comprehensive model of care through a patient-centered approach. Methods A descriptive analysis of the comprehensive care indicators of patients with type 2 diabetes treated in the CAIPaDi program between 2013 and 2023 was conducted. The results were structured according to the standard set of outcomes for diabetes proposed by the International Consortium for Health Outcomes Measurements (ICHOM). Results The baseline and prospective registration of consultations was completed for five years, complying with 25 of the 26 indicators of the ICHOM set. In diabetes control, 56.5% of patients had A1c ≤ 7%, 87.9% had BP ≤ 130/80 mmHg, 60.9% had LDL-cholesterol < 100 mg/dl, and obesity rates decreased from 42.19% to 30.6% during annual consultations. Fewer years of diagnosis before the first visit is key to overall improvement in program adherence (P = 0.02). In acute events, a hyperglycemic crisis occurred in only two cases and severe hypoglycemia episodes in 8 patients. For chronic complications, no lower limb amputations occurred. Cardiovascular outcomes occurred in < 1%. Periodontal disease was analyzed, and periodontitis decreased from 82.9% to 78.7%. Mortality reports were low, with COVID-19 being the main cause of death. Patient-reported outcomes demonstrated reductions in anxiety, depression, and diabetes distress during follow-up. Conclusion Registering quality-of-care indicators is feasible in a comprehensive care program. It allows improving the medical, mental health, and lifestyle outcomes of patients with type 2 diabetes and provides relevant data for planning health programs. A quick diagnosis before program adherence is crucial for overall improvement in patients.